Factors sociodemographic intra and extra organizational related to Burnout syndrome in health professionals in hospitals. Ancash. Peru.2011 - Yslado, Rosario (2011)
It is a descriptive correlational research, the aim was to analyzeand relatefactors sociodemographic, intra and extra organizational, with syndrome of burning  for the work(SBW)) of doctors, nurses (as) and obstetrician sof five hospitals from Ancash.The sample was 127 appointed professionals, 54 doctors, 57 nurses and 16 midwives, of both sexes,between 25 and 69 years old. It was applied the questionnaire syndrome burned by work in health care,DIRES Ancash -2011,validated by criteria of judges and pilot study,and MBI –MaslachBurnoutInventory. It was found that the majority(78.0%) of health professionals haveearly phase of burnout, low stress, and 2.4% are in the intermediate phasea nd 19.6% in the final phase,highstress chronic work and burnout. There are significant differences between occupational groups in relation to the dimension low personal realization, that doctors have a higher percentage.There are also significant differences by gender, the male have moreoften low personal realization at work.No were found significant differences for emotional exhaustion and depersonalization dimensions. In conclusion there isnt significant association between factor ssociodemographic, intra and extraorganizational with burnout in all its phases, but if there is significant relationship between factor intraorganizational group(support social-emotional, interpersonal conflicts with coworkers,guild conflicts) and final phase of burnout in the professionals groups mentioned.